Estimating Solar Irradiance Since 850 CE. Issue 4 (20th April 2018) - Lean, J. L.
Abstract: Solar total and spectral irradiance are estimated from 850 to 1610 by regressing cosmogenic irradiance indices against the National Oceanic and Atmospheric Administration Solar Irradiance Climate Data Record after 1610. The new estimates differ from those recommended for use in the Paleoclimate Model Intercomparison Project (PMIP4) in the magnitude of multidecadal irradiance changes, spectral distribution of the changes, and amplitude and phasing of the 11‐year activity cycle. The new estimates suggest that total solar irradiance increased 0.036 ± 0.009% from the Maunder Minimum (1645–1715) to the Medieval Maximum (1100 to 1250), compared with 0.068% from the Maunder Minimum to the Modern Maximum (1950–2009). PMIP4's corresponding increases are 0.026% and 0.055%, respectively. Multidecadal irradiance changes in the new estimates are comparable in magnitude to the PMIP4 recommendations in the ultraviolet spectrum (100–400 nm) but somewhat larger at visible (400–700 nm) and near‐infrared (700–1, 000 nm) wavelengths; the new estimates suggest increases from the Maunder Minimum to the Medieval Maximum of 0.17 ± 0.04%, 0.030 ± 0.008%, and 0.036 ± 0.009% in the ultraviolet, visible, and near‐infrared spectral regions, respectively, compared with PMIP4 increases of 0.17%, 0.021%, and 0.016%. The uncertainties are 1 σ estimates accruing from the statistical procedures that reconstruct irradiance in the Medieval Maximum relative to the Modern Maximum, not from the specification of Modern Maximum irradiances per se. In the new estimates, solar irradiance cycle amplitudes in the Medieval Maximum are comparable to those in the Modern Maximum, whereas in the PMIP4 reconstruction they are at times almost a factor of 2 larger at some wavelengths and differ also in phase. Key Points: Solar irradiance is newly estimated from 850 to 1610, consistent with the NOAA Solar Irradiance Climate Data Record from 1610 to 2016 Multidecadal changes from grand minima to grand maxima are larger than in the Paleoclimate Model Intercomparison (PMIP4) recommendations Solar cycle amplitudes are smaller than in the PMIP4 irradiances and differ in phase